1972
DOI: 10.1037/h0033115
|View full text |Cite
|
Sign up to set email alerts
|

Strong Vocational Interest Blank and Kuder Occupational Interest Survey differences reexamined in terms of Holland's vocational theory.

Abstract: Attempted to reconcile differences reported in previous studies between the SVIB and Kuder Occupational Interest Survey (OIS) by interpreting a factor analysis of like-named scales in terms of J. Holland's theory of vocational choice. When the scales in the OIS and SVIB factors were assigned Holland 3-letter codes, the similarities among the factors became evident. The Holland system facilitated the naming of the factors and provided possible explanations for low correlations between like-named scales. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Factor analytic research with white subjects (Campbell, 1974;Cole & Hanson, 1971;O'Shea & Harrington, 1972) has shown that Holland's (1973) hexagonal model explains most of the variance being measured by interest inventories. Holland's model is also closely related to Guilford, Christensen, Bond, and Button's (1954) comprehensive analysis of human interests, which identified six major factors-mechanical, scientific, social welfare, clerical, business, and aesthetic.…”
mentioning
confidence: 99%
“…Factor analytic research with white subjects (Campbell, 1974;Cole & Hanson, 1971;O'Shea & Harrington, 1972) has shown that Holland's (1973) hexagonal model explains most of the variance being measured by interest inventories. Holland's model is also closely related to Guilford, Christensen, Bond, and Button's (1954) comprehensive analysis of human interests, which identified six major factors-mechanical, scientific, social welfare, clerical, business, and aesthetic.…”
mentioning
confidence: 99%
“…Holland's theory argues that every individual seeks out and is drawn to environments that suit their personality types. For instance, a person with the enterprising personality type will look for a profession in the entrepreneurial sector (O'Shea & Harrington, 1972). Six Holland's occupational types are listed: (R) Realistic: qualified, technical, and some service professions; (I) Investigative: scientists and some technical professions; (A) Artistic: professions in the sphere of music, literature; (S) Social: education and professions related to social care; (E) Enterprising: managerial positions and commercial services; (C) Conventional: includes office and white-collar jobs.…”
Section: Theoretical Foundations Of Research Holland's Model and Its ...mentioning
confidence: 99%
“…The research includes John Holland's Theory of Career Choice (RIASEC) (Holland, 1970a, as cited in O'Shea & Harrington, 1972), Schwartz's theory of basic values and its structure (Schwartz, 2012). Students' values are expected to be directly related to their choice of studies based on the assumptions of Holland's Theory of Career Choice (RIASEC) (O'Shea & Harrington, 1972). Also, the research by Berring et al (2015), Sababa and Benson (2010), and the author's interviews with the respondents are used to support the hypothesis that the Turkish students' group has greater preferences for choosing science than the Polish students' group.…”
mentioning
confidence: 99%
“…The CDM authors were originally influenced by factor analytic research with White American participants (Campbell, 1974;Cole & Hanson, 1971;O'Shea & Harrington, 1972) that showed that the RIASEC model explained most of the variance being measured by inventories. At that time, only a few studies were found that compared the vocational interests of non-Whites with those of Whites.…”
mentioning
confidence: 99%